Facile synthesis and adsorptive removal of rhodamine b dye from aqueous medium using green synthesized nanocomposite - Gbawoquiya, Flomo L.; Rachna, Kumari; Narayanan, Shankara S.; Singh, Pramod K.; Shankar, Shiv; Mohd Noor, Ikhwan Syafiq; Yahya, Muhd Zu Azhan (Engineers Society for Corrosion, 2024)
Reduced graphene oxide (rGO) and zinc oxide nanoparticles (ZnO NPs) were synthesized using modified Hummer's method and green approach from Carica papaya leaf extract (CPLE), respectively. ZnO NPs were then loaded onto rGO using a straightforward ultrasonic method to synthesize Zinc oxide-reduced graphene oxide nanocomposite (ZnO-rGO NC). Fourier Transform Infrared Spectroscopy (FTIR), Field Emission Scanning Electron Microscopy (FESEM), and X-ray diffraction (XRD) techniques were used to characterize the synthesized nanoparticles and composite respectively. The nanocomposite was used to remove Rhodamine B dye (RhB) from aqueous solution. The effects of temperature, pH, adsorbent dosage, initial dye concentration, and contact time were investigated. Testing was done on the Freundlich and Langmuir isotherm models as well and the thermodynamics parameters were computed. The effects of ZnO NPs, rGO, and ZnO-rGO NC independently on dye removal in a comparative analysis were carried out and resulteds were presented. In an aqueous medium, the nanocomposite demonstrated high removal efficiency as an adsorbent for removing RhB dye at 99% compared to ZnO NPs at 60%. ZnO-rGO NC proved to be an effective adsorbent compare to ZnO NPs.